Salt-activated bimetal–phenolic nanoadhesive for broad-spectrum micro- and nanoplastic removal across salinity gradients - Zheng Cai; Qingfeng Yao; Lan Zhao; Yan Cao; Yishuang Li; Xianluo Hu; Jingming Gong (Chemical Engineering Journal, 2026)

Key exposure components and oxidative stress-driven health risks assessment of oil mist generated by metalworking fluids in industrial building environment - Yang Yang; Yilin Li; Yuming Zhang; Yi Wang; Yalin Liu; Ming Liu; Xudong Li; Yifan Qu; Mengdan Qiao; Qingfeng Cao (Journal of Hazardous Materials, 2026)

Lymph node-targeted H2S-self-releasing multifunctional prodrug for the dual remodeling of immunological and redox homeostasis in autoimmune uveitis - Qinjin Dai; Yuelan Wu; Wenbo Geng; Mengna Li; Wanyun Zhang; Yuxian Lai; Pei Zhang; Xiaoyue Zhang; Chunjiang Zhou; Yinuo Wang; Qingfeng Cao; Xiang Luo; et al. (Chemical Engineering Journal, 2026)

Large-scale PM2.5 removal and CO2 direct air capture to mitigate ambient air pollution and combat global climate change - David Y.H. Pui; Qingfeng Cao; Thomas Kuehn; Charles Lo; Sheng-Chieh Chen (Journal of Environmental Sciences, 2026)

Exploring the polymorphism of foxtail millet proteins and the mechanisms of activity variations driven by varietal differences - Zeyu Peng; Jia Cao; Hongyue Zhao; Bowen Yang; Jianjun Cheng; Qingfeng Ban (Food Research International, 2026)

Inferring irrigation regimes and sunshine duration from the distribution and spectral characteristics of farmland microplastics - Hangzheng Zhao; Xu Han; Changming Cao; Ziyi Zan; Bo-Tao Zhang; Jiamin Wang; Qingfeng Tang; Weifeng Yue; Yan Liu (Environmental Pollution, 2026)

Seep-related carbonates on continental shelves: Distinctive processes and morphologies revealed by the Qiongdongnan Shelf, South China Sea - Hongli Wang; Qiang Zhao; Fangqi Wang; Qingfeng Hua; Qiuhong Xie; Yangting Liu; Chenguang Liu; Yanliang Pei; Xishuang Li; Yikai Feng; Fei Cao (Marine Geology, 2026)

Evolution of plumes from a composite plate–cylinder heat source under buoyancy–shear driven conditions - Ningbin Zhu; Yang Yang; Mengdan Qiao; Yi Wang; Qingfeng Cao; Yong Cui; Yuming Zhang; Sikang Li (Building and Environment, 2026)

Resistance characteristics of irregular exhaust hoods and inverse design based on airflow distribution in rolling mills - Qingfeng Cao; Yang Yang; Zhaolan Zhang; Yi Wang; Kangning Xiong; Yong Cui; Yuming Zhang; Sikang Li; Ning Lei (Journal of Cleaner Production, 2026)

Synergistic optimization of filter bag arrangement and shape for vortex suppression flow equalization and resistance reduction in a straight-through baghouse dust collector - Qingfeng Cao; Yang Yang; Yi Wang; Kangning Xiong; Ningbin Zhu; Yong Cui; Yuming Zhang; Sikang Li (Journal of Cleaner Production, 2026)

Effects of protein structure and proteomics on the moisture migration in rice with milling degrees - Jia Cao; Zeyu Peng; Lina Sun; Ruobing Jia; Bowen Yang; Jianjun Cheng; Qingfeng Ban; Huan Wang (Food Research International, 2026)

Pressure drop reduction of filter media for oily aerosol: progress and prospects - Yong Cui; Yang Yang; Kangning Xiong; Yi Wang; Qingfeng Cao; Sikang Li; Yuming Zhang (Energy and Buildings, 2026)

Two-phase structure optimization of Al-doped Ag1.995Te0.5S0.5 for improved mechanical and thermoelectric properties - Min Zhu; Xiao-Lei Shi; Hao Wu; Meng Li; Wei-Di Liu; De-Zhuang Wang; Liang-Cao Yin; Wen-Yi Chen; Yan Huang; Zhi-Gang Chen; Qingfeng Liu (Chemical Engineering Journal, 2026)

Diffusion of micron-sized oil droplets accompanying short-term thermal airflow with weak buoyancy in machining intervals - Yuming Zhang; Yang Yang; Yi Wang; Jia-ning Fan; Tongtong Zhao; Jun Gao; Qingfeng Cao; Ningbin Zhu; Yong Cui (Building and Environment, 2026)

Preliminary application of synchrotron time-resolved SAXS in in-situ study of dust explosion - Haijuan Wu; Jiahao Liu; Xiaolan Ji; Wenmin Li; Longlong Yang; Yingfeng Sun; Qingfeng Qin; Zhihong Li; Xiong Cao; Yixin Zhao (Fuel, 2026)

Intensification of Weddell Sea deep water in the southern Scotia Sea since ∼0.4 Ma: Mechanistic links to the mid-Brunhes transition - Qiang Zhao; Hongli Wang; Yanpeng Zheng; Kai Liu; Xishuang Li; Chenguang Liu; Yanliang Pei; Qingfeng Hua; Long Ma; Yonghua Wu; Shulan Ge; Fei Cao; et al. (Quaternary Science Reviews, 2025)

A physics-informed neural network integrating physical mechanisms and experimental data for predicting VOCs emission rates in machining workshops - Mengdan Qiao; Yang Yang; Ningbin Zhu; Yi Wang; Sikang Li; Qingfeng Cao; Yanghui Hou; Bo Qian (Building and Environment, 2025)

In situ study of the effect of ignition delay time on the lignite dust explosion using synchrotron radiation time-resolved SAXS - Xiaolan Ji; Jiahao Liu; Haijuan Wu; Longlong Yang; Wenmin Li; Yingfeng Sun; Qingfeng Qin; Zhihong Li; Lili Dong; Yuanyang Wang; Yixin Zhao; Xiong Cao; et al. (Fuel, 2025)

Evaporation and settling of semi-synthetic metalworking fluid droplets in industrial buildings - Yuming Zhang; Yang Yang; Qingfeng Cao; Ningbin Zhu; Yong Cui; Yi Wang; Chaojie Wang (Building and Environment, 2025)

The impact of sub-pixel scale urban function on urban heat island: Insights derived from its decomposition - Qingfeng Guan; Yajun Li; Wenjia Huang; Wei Cao; Zhewei Liang; Jie He; Xun Liang (Applied Geography, 2025)

Association of PM2.5-bound multiple metals co-exposure with early cardiovascular damage: A panel study in young adults combining metabolomics - Junjie Chen; Qingfeng Zhou; Yingrong Wang; Yuting Wu; Miao Li; Haotian Wang; Guoying Zheng; Yulan Hao; Xiangke Cao; Wenqi Yang; Lei Zhang; Qian Wang (Environmental Pollution, 2025)

Large-scale dual-responsive ClO2 controlled-release film for strawberry preservation - Siqi Chen; Wenya Ma; Ying Cao; Kunpeng Qian; Qingfeng Dong; Li Li (Food Chemistry, 2025)

Occurrences, source apportionment, and potential risks of 55 progestins in surface water of the Yellow River Delta, China - Xiaoyan Shen; Qudi Zhang; Qingyue Xiang; Jiajun Zhao; Yue Cao; Kun Li; Jiayu Song; Zihao Wang; Xinkun Zhao; Qingfeng Chen (Journal of Hazardous Materials, 2024)

Distribution of oil mist particles and air quality improvement in the working area of the cutting workshop - Yuming Zhang; Yang Yang; Qingfeng Cao; Yi Wang; Jia-Ning Fan; Hu Chen; Xin Wang; Fei Wang; Yu Zhou; Mengfan Quan (Journal of Hazardous Materials, 2024)

Copper stearate-coated DAP-4 core–shell composites for enhanced safety and thermal decomposition performance - Xueli Zhang; Erhai An; Guangwei Xiao; Qingfeng Qin; Yingxin Tan; Peng Deng; Xiong Cao (Fuel, 2024)

Numerical Simulation of Self-Propelled Dive Motion of a Virtual Mooring Buoy - Hongyu Li; Huijie Cao; Jiayi Xu; Wenxin Li; Qingfeng Ma; Weizhuang Ma (Journal of Marine Science and Engineering, 2024)
To verify the feasibility of the variable wing actuator for a virtual mooring buoy, this paper investigates the self-propelled dive motion of a virtual mooring buoy under hydrostatic variable density conditions using a computational fluid dynamics (CFD) approach. The virtual mooring buoy developed by our research group is used in this study, and the numerical simulation is performed using the Reynolds-averaged Navier–Stokes (RANS) equation and the SST K-Omega turbulence model to capture the turbulent flow. Grid convergence studies were conducted at three grid resolutions to ensure the accuracy of the numerical simulations. The effects of different wing angles on the self-propelled dive motion of the buoy are focused on and analyzed. The results show that the maximum velocity of the buoy in the horizontal direction can reach 0.31 m/s, with a wing angle of −8°, which is about 35% higher than that of 0°, effectively enhancing the buoy’s anti-disturbance capability against the horizontal currents. In addition, this study further analyzes the self-propelled dive motion of the buoy with variable wing angles. The results show that the velocity and attitude of the buoy at any moment are basically the same as those under the corresponding fixed wing angle. This shows that it is possible to change the motion of the buoy by varying the wing angle, verifying the feasibility of the variable wing actuator.

A repertoire of single nucleotide polymorphisms (SNPs) of major fecundity BMPR1B gene among 75 sheep breeds worldwide - Chunna Cao; Qian Zhou; Yuxin Kang; Zhanerke Akhatayeva; Peiyao Liu; Yuheng Bai; Ran Li; Yu Jiang; Qingfeng Zhang; Xianyong Lan; Chuanying Pan (Theriogenology, 2024)

Vertically designed high-performance and flexible thermoelectric generator based on optimized PEDOT:PSS/SWCNTs composite films - Binjie Xia; Xiao-Lei Shi; Li Zhang; Jia Luo; Wen-Yi Chen; Boxuan Hu; Tianyi Cao; Ting Wu; Wei-Di Liu; Yanling Yang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2024)

Correction to: Clinical Significance and Influencing Factors of Microvascular Tissue Reperfusion After Macrovascular Recanalization - Xuesong Bai; Fan Yu; Qiuyue Tian; Wei Li; Arman Sha; Wenbo Cao; Yao Feng; Bin Yang; Yanfei Chen; Peng Gao; Yabing Wang; Jian Chen; et al. (Translational Stroke Research, 2023)

Biotechnology Remediation and Environmental Behavior of Microplastics in Soils: A Review - Weiying Feng; Yuxin Deng; Yingnan Cao; Jing Liu; Yunping Han; Jianguo Liu; Qingfeng Miao; Fang Yang; Ying Zhu; John P. Giesy (Reviews of Environmental Contamination and Toxicology, 2023)

Clinical Significance and Influencing Factors of Microvascular Tissue Reperfusion After Macrovascular Recanalization - Xuesong Bai; Fan Yu; Qiuyue Tian; Wei Li; Araman Sha; Wenbo Cao; Yao Feng; Bin Yang; Yanfei Chen; Peng Gao; Yabing Wang; Jian Chen; et al. (Translational Stroke Research, 2023)

Purification technology of oil mist in industrial buildings: A review - Yang Yang; Hu Chen; Qingfeng Cao; Mengdan Qiao; Yi Wang; Jia-Ning Fan; Chunhui Yang; Bo Pan; Xin Wang; Fei Wang; Wenchao Ju; Yu Zhou (Building and Environment, 2023)

Comparative genomic analysis of Mycoplasma anatis strains - Qi Zhou; Kaijie Mai; Dehong Yang; Junfa Liu; Zhuanqiang Yan; Cuifen Luo; Yangtong Tan; Sheng Cao; Qingfeng Zhou; Li Chen; Feng Chen (Genes & Genomics, 2021)

Structure-based design, synthesis, PPAR-γ activation, and molecular docking of N-substituted phthalimides - Bin Xiao; Shumin Wang; Zhanfei She; Qingfeng Cao; Na Zhao; Xiangrong Tian; Yixin Su (Medicinal Chemistry Research, 2017)

A new azaphilone from the entomopathogenic fungus Hypocrella sp. - Qingfeng Guo; Lili Dong; Xiangyun Zang; Zijian Gu; Xiaoyun He; Lindan Yao; Liping Cao; Junzhi Qiu; Xiong Guan (Natural Product Research, 2015)

Fluorescence and HPLC Detection of Hydroxyl Radical by a Rhodamine-Nitroxide Probe and its Application in Cell Imaging - Linying Cao; Qingfeng Wu; Qiang Li; Shijun Shao; Yong Guo (Journal of Fluorescence, 2014)

An improved reverse transcription loop-mediated isothermal amplification assay for sensitive and specific detection of Newcastle disease virus - Qiang Li; Chunyi Xue; Jianping Qin; Qingfeng Zhou; Feng Chen; Yingzuo Bi; Yongchang Cao (Archives of Virology, 2009)